Vapor phase fabrication of three‐dimensional arrayed BiI3 nanosheets for cost‐effective solar cells. Issue 5 (17th December 2019) - Zhu, Yiyi; Zhang, Qianpeng; Kam, Matthew; Poddar, Swapnadeep; Gu, Leilei; Liang, Shijun; Qi, Pengfei; Miao, Feng; Fan, Zhiyong
Abstract: Multilayered photovoltaic absorbers have triggered widespread attention for their unique structure and properties. However, multilayered materials in the randomly oriented polycrystalline thin‐film lead to ineffective carrier transport and collection, which hinders the process of achieving high‐performance solar cells. Herein, this issue is tackled by producing the three‐dimensional (3D) heterojunction BiI3 nanosheets (NSs) solar cells, which embed vertically aligned monocrystalline BiI3 NSs into spiro‐OMeTAD. The preferred orientation of BiI3 NSs and large p‐n junction areas of 3D heterojunction structure enable a strong light absorption and effective carrier transport and collection, and thus a power conversion efficiency (PCE) of 1.45% was achieved. Moreover, this PCE is the highest ever reported for BiI3 based solar cells to our best knowledge. Moreover, the nonencapsulated device remained 96% of the initial PCE after 24 h continuous one sun illumination at ~70% humidity condition, and 82% of the initial PCE after 1‐month storage at ~30% humidity condition. Abstract : The issue of ineffective carrier transport and collection of multilayered materials in the randomly oriented polycrystalline thin‐film is tackled by producing the 3D heterojunction BiI3 NSs solar cells, which embed vertically aligned monocrystalline BiI3 NSs into spiro‐OMeTAD. The preferred orientation of BiI3 NSs and large p‐n junction areas enable a strong light absorption and effective carrier transport and collection.